2020
DOI: 10.1186/s13063-020-04860-8
|View full text |Cite
|
Sign up to set email alerts
|

Digital crowdsourced intervention to promote HIV testing among MSM in China: study protocol for a cluster randomized controlled trial

Abstract: Background Men who have sex with men (MSM) are an important HIV key population in China. However, HIV testing rates among MSM remain suboptimal. Digital crowdsourced media interventions may be a useful tool to reach this marginalized population. We define digital crowdsourced media as using social media, mobile phone applications, Internet, or other digital approaches to disseminate messages developed from crowdsourcing contests. The proposed cluster randomized controlled trial (RCT) study aims to assess the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
(42 reference statements)
1
5
0
1
Order By: Relevance
“…However, our ndings were consistent with ndings from the 2016 national survey on SMY in China, which reported that only a low proportion of SMY encountered di culties when receiving health care services [28]. Past efforts to implement HIV prevention interventions targeting men who have sex with men (MSM) in China to increase awareness of safe male-male sex [29][30][31] may have contributed to higher SRH awareness and higher SRH services utilization in gay men, explaining our ndings. Whilst the ndings of this study suggests that SMY have relatively better SRH services utilization than heterosexuals, it is important to note that the absolute rate of SRH services utilization was still low, indicating that the majority of SMY do not have access to appropriate SRH services.…”
Section: Discussionsupporting
confidence: 89%
“…However, our ndings were consistent with ndings from the 2016 national survey on SMY in China, which reported that only a low proportion of SMY encountered di culties when receiving health care services [28]. Past efforts to implement HIV prevention interventions targeting men who have sex with men (MSM) in China to increase awareness of safe male-male sex [29][30][31] may have contributed to higher SRH awareness and higher SRH services utilization in gay men, explaining our ndings. Whilst the ndings of this study suggests that SMY have relatively better SRH services utilization than heterosexuals, it is important to note that the absolute rate of SRH services utilization was still low, indicating that the majority of SMY do not have access to appropriate SRH services.…”
Section: Discussionsupporting
confidence: 89%
“…In 2019, with support of the National Key Science and Technology fund, the Chinese CDC cooperated with Blued, a Chinese gay dating app used in China ( 1 ), to set up a HIV booking platform called “Happy Testing”. Here, MSM could choose AHTS sites nearby (CDCs or NGOs) for HIV services.…”
Section: Methodsmentioning
confidence: 99%
“…In China, HIV (human immunodeficiency virus) has become an epidemic among men who have sex with men (MSM) and poses a serious public health challenge ( 1 , 2 ). Although China has improved the prevention of HIV through prophylaxis treatments and prevention strategies, its prevalence was estimated to be 6% in 2020 ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to conventional approaches, crowdsourcing may facilitate community engagement, while creating novel solutions to public health problems that resonate with the community [ 22 ]. In particular, crowdsourcing can help engage vulnerable groups who are often excluded from research projects [ 23 ]. However, most crowdsourced interventions in sexual health research centered on HIV testing services and promoting sexual health programs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%